Synthesis and biological evaluation of (phenylpiperazinyl-propyl)arylsulfonamides as selective 5-HT2A receptor antagonists - Yoo, Euna; Yoon, Juhee; Pae, Ae Nim; Rhim, Hyewhon; Park, Woo-Kyu; Kong, Jae Yang; Choo, Hea-Young Park (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
A novel series of 5-HT2A ligands that contain a (phenylpiperazinyl-propyl)arylsulfonamides skeleton was synthesized. Thirty-seven N-(cycloalkylmethyl)-4-methoxy-N-(3-(4-arylpiperazin-1-yl)propyl)arylsulfonamide and N-(4-(4-arylpiperazin-1-yl)butan-2-yl)-arylsulfonamide compounds were obtained. The binding of these compounds to the 5-HT2A, 5-HT2C, and 5-HT7 receptors was evaluated. Most of the compounds showed IC50 values of less than 100 nM and exhibited high selectivity for the 5-HT2A receptor. Among the synthesized compounds, 16a and 16d showed good affinity at 5-HT2A (IC50 = 0.7 nM and 0.5 nM) and good selectivity over 5-HT2C (50-100 times) and 5-HT7 (1500-3000 times). (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: SEROTONIN; DERIVATIVES; SCHIZOPHRENIA; AFFINITY